Application Of Bioreeftech to Preserve Marine Ecosystems - Nugrahening Widhi (Indoneisa), Raut; Wahyuning Paluphi (Indonesia), Ratu; Aksa Aziz (Indonesia), Muh. (JURNAL KASTARA, 2024)
Abstract Coral reefs are one of the most productive and diverse ecosystems in the world. Still, their existence continues to be threatened by various environmental pressures such as climate change, pollution, and human activities. Restoration is an important solution to restore degraded ecosystems, one of which is using Bioreeftek technology. This study aims to evaluate the effectiveness of Bioreeftek as an artificial substrate in supporting coral reef restoration at the service location. Activities are carried out by selecting the right location based on physical, chemical, and biological parameters, installing the Bioreeftek structure, and monitoring initial results. The evaluation results show that Bioreeftek has good structural stability. Bioreeftek has proven effective in supporting the coral reef restoration process, with great potential for application in other locations with similar environmental characteristics.